Prince on the art of power - "Machiavelli, Niccolo" (London, 2007)
Frequently misunderstood over the centuries as an unprincipled manual for manipulators and tyrants, careful reading of "The Prince" shows that it identifies freedom as an essential characteristic of a good society - Machiavelli sets out axioms for success and order amid the often violent political intrigues that characterized Renaissance Europe. Combining fine photographic illustrations with a new translation of one of the great literary works of history, this classic text examines the relationship between moral goodness and legitimate authority, setting out timeless principles for pursuing power and fortune and using them to best effect in securing order and peace. Much of Machiavelli's republican thought can be identified in the American constitution, and many of his ideas - such as the belief that life is subject to change and that the winners will be those flexible enough to adapt - remain as applicable today as they were half a millennium ago.
Keywords: Political Science